Effects of heat and drought stress on post‐illumination bursts of volatile organic compounds in isoprene‐emitting and non‐emitting poplar. (18th January 2016) - Jud, Werner; Vanzo, Elisa; Li, Ziru; Ghirardo, Andrea; Zimmer, Ina; Sharkey, Thomas D.; Hansel, Armin; Schnitzler, Jörg‐Peter
Abstract: Over the last decades, post‐illumination bursts (PIBs) of isoprene, acetaldehyde and green leaf volatiles (GLVs) following rapid light‐to‐dark transitions have been reported for a variety of different plant species. However, the mechanisms triggering their release still remain unclear. Here we measured PIBs of isoprene‐emitting (IE) and isoprene non‐emitting (NE) grey poplar plants grown under different climate scenarios (ambient control and three scenarios with elevated CO2 concentrations: elevated control, periodic heat and temperature stress, chronic heat and temperature stress, followed by recovery periods). PIBs of isoprene were unaffected by elevated CO2 and heat and drought stress in IE, while they were absent in NE plants. On the other hand, PIBs of acetaldehyde and also GLVs were strongly reduced in stress‐affected plants of all genotypes. After recovery from stress, distinct differences in PIB emissions in both genotypes confirmed different precursor pools for acetaldehyde and GLV emissions. Changes in PIBs of GLVs, almost absent in stressed plants and enhanced after recovery, could be mainly attributed to changes in lipoxygenase activity. Our results indicate that acetaldehyde PIBs, which recovered only partly, derive from a new mechanism in which acetaldehyde is produced from methylerythritol phosphate pathway intermediates, driven by deoxyxylulose phosphate synthase activity. Abstract : We investigated how combined heat and drought stress under elevated CO2 impact post illumination emissions of volatile organic compounds (VOCs) from isoprene emitting (IE) and isoprene non‐emitting (NE) poplar leaves. While in general stress is thought to induce the release of green leaf volatiles (GLV) we observed the opposite ‐ a suppression of GLV and acetaldehyde post illumination bursts (PIB) as well as a reduction in lipoxygenase (LOX) activity during heat and drought stress. The observed reduction of these short‐term stimulated pulses of GLV and acetaldehyde in environmentally challenged plants could be used as fast and non‐invasive markers in plant phenotyping applications.